New Zealand Environmental History: A Question of Attitudes. (1st November 2003) - Star, Paul
Abstract : As a land to which not only Europeans, but also humans of any kind, came late, New Zealand is a fascinating case study in environmental history. The author's own research into the early years of European settlement plots an evolving cultural engagement with the indigenous environment, and in particular with forest or 'bush', which ran parallel with its extensive replacement by agroecosystems. Research of this character must now be closely compared with work done overseas - perhaps initially with Australian studies. Only by drawing out the unique features of each case will the respective roles of environment and culture in the history of New Zealand, and of other countries, be fairly determined.